Advancing a temporal framework for understanding the biology of nonsuicidal self- injury: An expert review. (November 2021) - Kaess, Michael; Hooley, Jill M.; Klimes-Dougan, Bonnie; Koenig, Julian; Plener, Paul L.; Reichl, Corinna; Robinson, Kealagh; Schmahl, Christian; Sicorello, Maurizio; Westlund Schreiner, Mindy; Cullen, Kathryn R.
Highlights: Nonsuicidal self-injury (NSSI) is a serious clinical problem. The biological aspects of NSSI are reviewed and synthesized in a conceptual model. Distal biological traits, proximal biological traits, and biological states are distinguished. Recommendations for future research on the neurobiology of NSSI are provided. Abstract: Nonsuicidal self-injury (NSSI) is a serious clinical problem, particularly for adolescents and young adults. NSSI is a complex behavior that emerges through the intersecting effects of social, psychological, and biological mechanisms. Although the social and psychological contributions to risk for developing NSSI are relatively well understood and have guided the development of effective psychosocial treatments for self-injury, the biological mechanisms underlying NSSI have just begun to come to light. To evaluate and categorize the biological research conducted on the topic of NSSI, we propose a model that distinguishes between trait and state markers. According to this model, risk factors and mechanisms involved in NSSI can be distinguished into both trait and state factors. We review the existing evidence on distal biological traits (predictors) of NSSI, proximal biological traits (correlates) of NSSI, and biological states directly preceding or following NSSI. We conclude by providing recommendations for future research on the neurobiology of NSSI.